2006
DOI: 10.1152/ajplung.00340.2005
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane A2induces airway constriction through an M3muscarinic acetylcholine receptor-dependent mechanism

Abstract: Thromboxane A2 (TXA2) is a potent lipid mediator released by platelets and inflammatory cells and is capable of inducing vasoconstriction and bronchoconstriction. In the airways, it has been postulated that TXA2 causes airway constriction by direct activation of thromboxane prostanoid (TP) receptors on airway smooth muscle cells. Here we demonstrate that although TXA2 can mediate a dramatic increase in airway smooth muscle constriction and lung resistance, this response is largely dependent on vagal innervatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 56 publications
3
37
0
Order By: Relevance
“…To begin to address this possibility, we examined the change in airway responsiveness of the 129/SvEv GPRA Ϫ/Ϫ mice and their genetic controls to thromboxane. Previous studies have demonstrated that the increase in airway and tissue resistance in the mouse in response to this agent is dependent on an intact cholinergic pathway (2). As seen in Fig.…”
Section: Fig 4 Allergic Airway Inflammation In Wild-type and Gpramentioning
confidence: 80%
See 1 more Smart Citation
“…To begin to address this possibility, we examined the change in airway responsiveness of the 129/SvEv GPRA Ϫ/Ϫ mice and their genetic controls to thromboxane. Previous studies have demonstrated that the increase in airway and tissue resistance in the mouse in response to this agent is dependent on an intact cholinergic pathway (2). As seen in Fig.…”
Section: Fig 4 Allergic Airway Inflammation In Wild-type and Gpramentioning
confidence: 80%
“…The difference appears to be confined to the central airways, as no significant difference was observed in the G and H parameters, which are sensitive to changes in the distal lung. Previous studies have demonstrated that U-46619 facilitates airway smooth muscle constriction through an M 3 muscarinic acetylcholine receptor-dependent mechanism (2). It has been suggested that this mechanism likely involves afferent and efferent neural signaling (1,2,15).…”
Section: Discussionmentioning
confidence: 97%
“…Also, TxB 2 was abundant in the conditioned media from both Mf types. TxA 2 is often described as proinflammatory (e.g., in muscarinic acetylcholine receptor-mediated airway constriction) (38). However, TxA 2 -TP signaling also modulated immunity to foreign antigens by negatively regulating dendritic cell-T cell interactions (39).…”
Section: Discussionmentioning
confidence: 99%
“…Thus AHR following the early asthmatic reaction is reversed by anticholinergics [141], and the bronchoconstrictor response of inhaled inflammatory mediators (e.g. histamine and thromboxane A 2 ) is, to a large extent, mediated by cholinergic pathways [141,159].…”
Section: Cholinergic Mechanismsmentioning
confidence: 99%